Tingkat Kepatuhan Penggunaan Ramuan Jamu Saintifik Hiperglikemia pada Pasien Diabetes Melitus di Rumah Riset Jamu Hortus Medicus B2P2TOOT Tawangmangu - Hartono; Ary Kusumastuti, Livia (Jurnal Farmasi (Journal of Pharmacy), 2019)
Diabetes mellitus is a degenerative disease caused by chronic metabolic disorders characterized by high blood sugar. The levels compliance with treatment therapy can improve the success of therapy. This research purpose to determine the level of patient compliance level of use of scientific herbal medicine hyperglycemia in diabetes mellitus in Hortus Medicus Herbal Medicine Research House B2P2TOOT Tawangmangu. This research is a descriptive research, using data collection namely purposive sampling. The instruments used for compliance testing using MMAS-8 questionnaire. Data studied inclued age, gender, type of medicine, education, occupation, duration of suffering, and level of patient compliance as well as factors related to compliance. Results research on 96 respondents showed that including the category levels of patient adherence to the use of scientific herbal medicine hyperglycemia was high 48%, moderate adherence rate of 43% and low adherence level of 9%. Based on the results of the study it can be concluded that compliance level of use of scientific herbal medicine hyperglycemia in diabetes mellitus in Hortus Medicus Herbal Medicine Research House B2P2TOOT Tawangmangu classified as high category 48%.